National Scientific-Practical Conference “Süyün-Bike: An Outstanding Woman and Ruler (to the history of Tatar States’ relations in the 16th century)” (Kasimov, November 12, 2015) » - Bulat Rakhimzyanov (Золотоордынское обозрение)
National Scientific-Practical Conference “Süyün-Bike: An Outstanding Woman and Ruler (to the history of Tatar States’ relations in the 16th century)” has been held in Kasimov on 12th November, 2015. The conference has been organized by the public organization “Kasimov Local Tatar National-Cultural Autonomy of the Ryazan Region” as well as by Sh.Marjani Institute of History of the Academy of Sciences of the Respublic of Tatarstan. The conference was supported by a grant from the Government of the Republic of Tatarstan (agreement no. 176/10 of 24.08.2015). The conference was conceived as the first phase of a larger project, the final of which will be the erection of a monument dedicated to Süyün-Bike in Kasimov (Russian Federation). By the will of events, Süyün-Bike, a daughter of Yusuf, the future ruler of the Nogay Horde, became the most famous among the Nogay wives of the Kazan khans. After the fall of Kazan, her fate was connected with Kasimov, where she spent her last years and apparently was buried. In summary, the personal life of this woman contains the entire history of the Tatar medieval world, which was quite controversial. It contains intrigues and desire to keep power at any cost, a variety of coalitions both with each other and with people of other faiths, and love, and hate, and betrayal, and the captivity, and life far from her homeland. Süyün-Bike sacrificed personal happiness for the happiness of others. A confirmation of this fact is provided both by the numerous legends about the Kazan tsarina, still hovering in the minds of the Tatar people, as well as by the architectural tower in Kazan named after the Kazan tsarina. Through the conference, its organizers sought to demonstrate to the Kasimov and Tatarstan public that Kazan and Kasimov had a number of similarities as well as differences. One of the similarities was that the noble Nogay women linked Kazan and Kasimov, one of them being Süyün-Bike. Her fate connected a number of late Golden Horde states, namely the Kazan and Kasimov khanates as well as her native Nogay Horde.